2020
DOI: 10.7717/peerj.10319
|View full text |Cite
|
Sign up to set email alerts
|

Age relationships with telomere length, body weight and body length in wild dugong (Dugong dugon)

Abstract: The ability to estimate age and determine the growth status of free-ranging dugongs (Dugong dugon) is vital to providing insight into the basic biology of this endangered species. Currently, age estimation in dugong carcasses relies on counting dentin growth layer groups (GLGs) in tusks, but a disadvantage is they need to be intact. We explored whether measures of telomere length could be used as an alternative approach to age estimation in dugongs given that in other species, telomere length and age are inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…Skin samples were extracted using DNA extraction kits according to manufacturer’s instructions (DNeasy Blood & Tissue Kit, Qiagen, Germany) at the Faculty of Veterinary Medicine, Chiang Mai University, and the DNA measured qualitatively and quantitatively by agarose gel electrophoresis and spectrophotometry, respectively 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Skin samples were extracted using DNA extraction kits according to manufacturer’s instructions (DNeasy Blood & Tissue Kit, Qiagen, Germany) at the Faculty of Veterinary Medicine, Chiang Mai University, and the DNA measured qualitatively and quantitatively by agarose gel electrophoresis and spectrophotometry, respectively 16 .…”
Section: Methodsmentioning
confidence: 99%
“…In northeast Brazil, the anthropogenic-mediated loss of birthing grounds (Parente et al, 2004) was linked to the increased chances of mother-calf separation, and calf stranding rates of Antillean manatees (Balensiefer et al, 2017). This phenomenon is also reflected in our dataset; calf carcasses (≤ 2m in length; see Marsh, 1980;Cherdsukjai et al, 2020) accounted for more than 45% of the records with biometric information (Table S1). The autopsy of a 1.4m male recovered within our study site in 2021 concluded that pre-mature mother-calf separation was the likely cause of death as the suckling calf presented with no signs of physical trauma or disease, and its stomach was full of milk and seagrass (S. Z. H. Ng and Z. Jaafar, pers.…”
Section: Discussionmentioning
confidence: 67%
“…The samples were processed using DNA extraction kits according to manufacturer's instructions (DNeasy Blood & Tissue Kit, Qiagen, Germany) at the Faculty of Veterinary Medicine, Chiang Mai University [32], and the DNA measured qualitatively and quantitatively by agarose gel electrophoresis and spectrophotometry, respectively [4].…”
Section: Dna Extractionmentioning
confidence: 99%
“…The dugong (Dugong dugon), order Sirenia, family Dugongidae, is the only herbivorous marine mammal in the world, with a diet consisting of seagrass [1]. Dugongs have a life span of around 60-70 years [2], sexual maturity at ~10-12 years of age [3], and reach adulthood at 20 years of age [4]. Seagrass is the main food source of dugongs [5][6][7][8], so degradation and disappearance of these meadows are major reasons for declining dugong populations.…”
Section: Introductionmentioning
confidence: 99%